"Atentados dignos de los negros días de la dictadura". Violencia policíaca y resistencia en la ciudad de México durante la década de 1920 - Ponce Hernández, Alejandro (El Colegio de México, A.C., 2023)
Through the concept of legitimacy, this article examines the underlying motives behind the generalized violence between the police and Mexico City residents during the 1920s. Based on judicial documents and newspaper articles, it concludes that these shows of force between gendarmes and citizens, which went both ways, were due to a set of six phenomena: 1) complicity between the police and criminals, 2) the discriminatory surveillance of the working class, 3) the repressive attitude of the state toward social protest, 4) abuses of authority and the everyday irresponsibility of the gendarmes, 5) the exhaustion of society with all this, and 6) the arrogance of the political elites regarding the police.